2011
DOI: 10.2478/s11536-011-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived health and psychological well-being among Serbian schoolchildren and adolescents: data from National Health Survey

Abstract: AbstractThe purpose was to determinate possible factors associated with psychosocial health through self-perceived health and psychological well-being among Serbian schoolchildren and adolescents. A cross-sectional study. The study is based on the 2006 National Health Survey of the population of Serbia. A total of 2,721 schoolchildren and adolescents were included. Face-to-face questionnaire and self-administered questionnaire were used for collection of data. For the assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
3
1
0
Order By: Relevance
“…Our study suggests that poor self-perception of health is more prevalent among males than females and this finding corroborates with previous studies (Jovic-Vranes, Jankovic, Vasic, & Jankovic, 2011 ; Kestila et al, 2006) . Sociodemographic factors such as living in extended family, unskilled employment of fathers, mothers who are housewives, poor parenting (lack of communication) and unfair treatment by parents were found out to be associated factors for poor self-perception.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study suggests that poor self-perception of health is more prevalent among males than females and this finding corroborates with previous studies (Jovic-Vranes, Jankovic, Vasic, & Jankovic, 2011 ; Kestila et al, 2006) . Sociodemographic factors such as living in extended family, unskilled employment of fathers, mothers who are housewives, poor parenting (lack of communication) and unfair treatment by parents were found out to be associated factors for poor self-perception.…”
Section: Discussionsupporting
confidence: 93%
“…Generally studies report a higher proportion of girls with poor self-perceived health ( Piko, 2007 ; Sweeting & West, 2003 ). Although this is in contrast to our study findings, it is consistent with finding from study conducted in Serbia ( Jovic-Vranes et al, 2011 ; Kestila et al, 2006 ; Sweeting & West, 2003 ). Different studies have reported availability of strong social support to adolescent girls, by elderly female members of their family ( Denton & Walters, 1999 ; Sunder, Ramos, Short, & Rosenthal, 2006 ) as a major mediating factor for this gender difference in self-perceived health.…”
Section: Discussionsupporting
confidence: 88%
“…Third, the perceived health state of the female college students participating in Pilates classes in this study had a positive effect on their psychological well-being, suggesting that the students who perceive themselves as physical healthy are psychologically healthy as well. Jovic-Vranes et al (2011) examined the relationship between perceived health state and psychological well-being and found that the higher one’s perception of one’s health state is, the more positive one’s perception of one’s interpersonal relationships, personal growth, life purpose, and autonomy will be, thereby supporting the results of this study. Therefore, it should be recognized that constantly emphasizing the health effects of dance in Pilates classes can become a mediator that will encourage the students to engage in activities that are desirable for their psychological well-being.…”
Section: Discussionsupporting
confidence: 71%
“…Most the previous studies in Serbia were exclusively focused on single risk factors [ 10 - 13 ]. This is the first study investigating the prevalence of concurrent health risk behaviours and its association with demographic and socio-economic determinants of health among adolescents in Serbia.…”
Section: Introductionmentioning
confidence: 99%